Comparative Study of DNA Barcoding and Mini-Barcoding based on COI Gene for Species Identification and Phylogeny of Formicidae Family (Insecta: Hymenoptera) - Kolondam, Beivy Jonathan; Tallei, Trina Ekawati; Koneri, Roni; Mamahit, Juliet Merry Eva (HAYATI Journal of Biosciences, 2025)
DNA barcoding and mini-barcoding are widely used to study insect biodiversity, including ants (Hymenoptera: Formicidae). This study evaluated the effectiveness of both approaches for species identification and phylogenetic inference in ants, with particular attention to the performance of universal primers during PCR amplification. Full-length DNA barcode (658 bp) and mini-barcode (127 bp) regions of the mitochondrial cytochrome c oxidase subunit I (COI) gene were retrieved from GenBank, aligned, and analysed with maximum-likelihood phylogenetics (1,000 bootstrap replicates) under the Tamura-Nei model. The universal DNA barcoding primers (Folmer's LCO1490 and HCO2198) showed generally good alignment with ant COI sequences. However, multiple nucleotide mismatches were observed in LCO1490, including one critical mismatch located within the GC clamp region. In contrast, the universal mini-barcoding primers (UniMinibarF1 and UniMinibarR1) showed critical mismatches at their 3′ ends, likely reducing PCR efficiency. Despite limitations associated with primer mismatches, both DNA barcoding and mini-barcoding are reliable for species identification. DNA barcoding and mini barcoding are both capable of distinguishing ants at the species level, regardless of the length of the sequences being compared. The same sequences have also been used for phylogenetic analysis, showing good ability to distinguish ant species based on phylogenetic tree reconstruction. The comparison of DNA barcoding and mini-barcoding in ants showed that longer sequences offered superior resolution for species identification and phylogenetic reconstruction. These findings underscore the need for primer optimisation in ant-specific applications and highlight the utility of both barcoding strategies for taxonomic and evolutionary studies.